Wykorzystanie metody DEA do pomiaru efektywności liceów ogólnokształcących w Szczecinie - Łukasz Brzezicki (Studia i Materiały)
The article measures the efficiency of 19 high schools in Szczecin in 2018 using two DEA (Data Envelopment Analysis) models focused on results. The Cross Efficiency model (CE) and Game Cross Efficiency model (GCE) were used to estimate cross-flow efficiency. The technical efficiency of high schools was analysed in terms of quantity (number of students) and quality (education rankings). Depending on the empirical model chosen, the number of students, graduates or ranking index and the average value of high schools baccalaureate were assumed as the results. In both cases, the number of pedagogical employees was taken into account for the inputs. The lowest efficiency in the areas, both in terms of quantity and quality, was observed in the case of LO Sport Championships in CMS. The highest values of efficiency in terms of the quantitative characteristics of education were achieved by the 1st High School, and as regards the qualitative aspect of education at the XIII High School. Schools that opted for non-cooperation strategies with other units would achieve a higher level of efficiency than in the case of cooperation of all educational institutions by 7 p.p. on average in terms of quantity and 3 p.p. in terms of quality.